2010
DOI: 10.1111/j.1365-2966.2010.16707.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the filamentary structure of the galaxy distribution at z∼0.8

Abstract: We study filamentary structure in the galaxy distribution at z∼ 0.8 using data from the Deep Extragalactic Evolutionary Probe 2 (DEEP2) Redshift Survey and its evolution to z∼ 0.1 using data from the Sloan Digital Sky Survey (SDSS). We trace individual filaments for both surveys using the Smoothed Hessian Major Axis Filament Finder, an algorithm which employs the Hessian matrix of the galaxy density field to trace the filamentary structures in the distribution of galaxies. We extract 33 subsamples from the SDS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…The typical width of the three filaments is (1.5−2.0) h −1 70 Mpc with local variations up to 3 Mpc. Choi et al (2010) observed similar values for a sample of high and low redshift filaments (z ∼ 0.8 and z ∼ 0.1, respectively) taken from the DEEP2 (Davis et al 2003) …”
Section: Width and Length Of The Filaments In Scl2243supporting
confidence: 50%
“…The typical width of the three filaments is (1.5−2.0) h −1 70 Mpc with local variations up to 3 Mpc. Choi et al (2010) observed similar values for a sample of high and low redshift filaments (z ∼ 0.8 and z ∼ 0.1, respectively) taken from the DEEP2 (Davis et al 2003) …”
Section: Width and Length Of The Filaments In Scl2243supporting
confidence: 50%
“…Bond et al (2010b);Choi et al (2010); Eardley et al (2015)), where three-dimensional positions can be accurately determined for all galaxies (at least up to the effect of peculiar velocities). However, determining accurate spectroscopic redshifts for individual galaxies is a very time-consuming operation, and often in astronomy we are forced to make do with datasets for which radial positions are very poorly measured, as is the case for photometric redshift surveys, or even completely unknown.…”
Section: Definitionmentioning
confidence: 99%
“…If the standard deviation of the fit to a candidate structure was less than 1.5 h −1 Mpc (comparable to or less than the typical thickness of filaments in simulations and observations; e.g. Colberg et al 2005;Akahori & Ryu 2010;Choi et al 2010;Vazza et al 2014), the structure was retained and classified as a filament. If not, the candidate structure was rejected.…”
Section: Data and Analysismentioning
confidence: 99%